We can solve this system of equations by substitution.
First, we can solve the second equation for y to get y = 6x.
Then, we can substitute this expression for y into the first equation:
x + y = 28
x + 6x = 28
Combining like terms, we have 7x = 28.
Dividing both sides by 7, we get x = 4.
Substituting this value for x back into the second equation, we can solve for y:
y = 6x
y = 6(4)
y = 24.
Therefore, the solution to the system of equations is x = 4 and y = 24.
Solve the system of equations by substitution.
x+y=28
y=6x
1 answer